Human Stem Cell Models Identify Targets of Healthy and Malignant Hematopoietic Regulation - Reid, Jennifer (My University, 2020)
Hematopoiesis is the highly regenerative process of producing billions of blood cells each day, including white blood cells, red blood cells, and platelets. Given the relatively short life span of these mature cells, hematopoiesis is dependent on stem and progenitor cells to generate renewed progeny, which represents a tightly regulated process. This includes cell intrinsic and external factors, and where dysregulation can lead to anemia and cancer. As such, the hematopoietic hierarchy has been intensely studied for nearly a century and represents a gold standard model of cell fate and developmental biology, in research and clinical applications. Cellular models, such as in vitro culture and human-mouse xenografts in vivo, have been developed to explain complex phenomena pertaining to hematopoiesis and also interrogate processes which are too invasive to study in humans. Hematopoietic generation is required beyond sustaining homeostasis, and progenitors can be damaged through cytotoxic injuries such as radiation and standard chemotherapy, and also undergo leukemic transformation. There are two main treatment modalities for leukemia patients (a) receiving a stem cell transplant, and (b) drug or radiation-based therapy. In the former, shortages of donors and stem cells has remained an unmet clinical need for decades. In the latter, selective targeting of genetic mutations has become a successful standard-of-care in leukemias such as chronic myelogenous leukemia and acute promyelocytic leukemia. However, in the most common adult hematologic malignancy, chronic lymphocytic leukemia (CLL), similar targeting therapies have not been developed. Altogether, shortages of stem cells from healthy donors, chemotherapy-induced immune dysfunction, and a lack of targeted therapies, all reinforce the immediate need for innovative cellular models to address these clinical problems. To generate additional sources of human hematopoietic progenitors for laboratory study, human PSCs have been used. Unlike hematopoietic progenitor cells collected from healthy and leukemic donors, human pluripotent stem cells (PSC) can be easily propagated and expanded in vitro. PSCs can generate hematopoietic progenitor cells, but they remain poorly understood and have not been robustly applied to solve the aforementioned deficiencies related to patient treatment. Importantly, the biological regulation of both hematopoiesis and PSCs has been experimentally confirmed to significantly deviate between humans and other animals, such as mice, further reinforcing the importance of human-specific cell models of hematopoiesis. Therefore, I hypothesized that human stem cell models provide a focused approach to interrogate the regulation of hematopoiesis from the apex of the hierarchy, which can be used to understand the promotion of healthy hematopoiesis and understand malignant transformation. Collectively, the data presented within this thesis offer a deeper conceptualization of human stem cell models and the deconvolution of several complex components of hematopoietic regulation. This work has revealed novel, clinically relevant, and actionable targets to ultimately enable the promotion of healthy hematopoiesis on multiple fronts.
Keywords: hematopoiesis; pluripotent stem cells; chronic lymphocytic leukemia; chemotherapy-induced myelosuppression; patient derived xenograft model; trisomy 12